Smartwatches in the assessment of heart failure patients in epidemiology and pathophysiology studies: A scoping review - Solenn Fabien; Sandra Waechter; Gbenga A. Kayode; Berno Müller; Marietta Roth; Friedrich Koehler (ESC Heart Failure)
Abstract A limited number of studies with smartwatches (SWs) investigated their potential in the field of heart failure (HF). The aim of this scoping review is to understand the extent of current literature on SWs in the HF population and the device's potential to improve disease management. The literature search was performed on PubMed and Embase in March 2024. Inclusion criteria included the use of commercialized SWs, HF diagnosis and peer‐reviewed publications. Articles were excluded if the SW was not the study intervention or was part of a broader intervention programme. Reviews, case reports and study protocols were excluded. Of 1200 identified articles, 13 were included in the scoping review, encompassing 1171 patients with HF, and findings were presented in a descriptive summary table. Validity of several SW‐collected physiological metrics was assessed against established technologies. Heart rate and step count measures were deemed moderately accurate in the HF population with Fitbit trackers (n = 5 patients, r = 0.54) and Garmin watches [n = 15 patients (mean age: 65.5 ± 12.6 years), concordance correlation coefficient (CCC) = 0.89 for Vivofit 1 and CCC = 0.92 for Vivofit 3], respectively, while calorimetry was the least reliable measurement [n = 19 patients (mean age: 65.1 ± 6.6 years), mean difference to indirect calorimeter: P = 0.01 for Fitbit Charge 2, P = 0.02 for Mio Slice]. Wrist‐worn activity trackers were positively received by patients with HF [91.3% of adherence in research setting (n = 70 patients, median age (IQR): 79 years (76–82)), and 64% in real‐world environment (n = 14 patients)] and their health‐care providers (six cardiologists out of six acknowledged the data's usefulness), although device ownership ranged from 10 to 50% among the HF population. Physical activity information collected from SWs was found to be valuable in assisting cardiologists with their New York Heart Association (NYHA) functional class assessment, which is known for its limited objectivity and reproducibility. Multiple studies found that SWs, especially Fitbit devices, successfully identified a pattern where the degree of exercise intolerance increased with higher NYHA classes. These findings suggested that activity trackers can objectively evaluate the severity of physical activity limitations. As the functional classification of patients influences treatment strategies, SWs could serve as a valuable tool to facilitate and optimize outpatient disease management. SWs could be used as a complement to standard monitoring in HF. With continuous technological advances, it will be valuable to follow the deployment of SWs and to investigate their contribution to increased patient safety and consequently to health care cost reductions.